HAPPINESS AND WORKING HOURS IN INDONESIA - Bayu Kharisma; Sutyastie Soemitro Remi; Ferry Hadiyanto; Ghefiran Abdurrahimdzan (Universitas Padjadjaran, 2020)
Humans strive to achieve happiness throughout their lives; thus, every activity has the goal of attaining happiness in mind. Happiness is an essential indicator of good livelihood for humans; if people are not happy, then the quality of life will be reduced. This paper aims to analyze the effect of working hours on happiness in Indonesia by using cross-section data sourced from the Indonesia Family Life Survey (IFLS) wave 5 of 2014. The model is divided into quadratic models and grouped working hours; the methods used in this paper were the ordered logit for the primary model and the ordinary least square for comparison. The results showed that a quadratic pattern of working hours, where initially working hours would increase happiness, but after reaching a certain peak point, the addition of working hours would cause a decrease in happiness. This shows the existence of the Inversed U-Shaped pattern between working hours and happiness.